PROFESIONALISME GURU DALAM MENINGKATKAN KUALITAS PROSES PEMBELAJARAN MELALUI KOMPETENSI, KETELADANAN, DAN KEPEMIMPINAN HUMANIS DI SEKOLAH - Mahmud, Chusnul Mar’iyah; Nisa, Kartini Rahman (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The challenges of 21st-century education demand the strengthening of teacher professionalism beyond academic aspects, especially in schools with limited resources such as SMA Negeri 1 Waigete. This study aims to analyze the implementation of teacher professionalism in improving the quality of learning through competence, exemplary behavior, and humanistic leadership. Using a descriptive qualitative approach, the research stages, conducted in January 2026, included in-depth interviews, observations, and documentation with the principal and teachers selected through purposive sampling. The research findings indicate that professionalism is reflected in teacher involvement in school development and the management of emotional and social intelligence. The use of lectures, small group discussions, and practicums has been shown to increase active participation and student discipline. Despite facing obstacles such as low learning motivation and diverse student characters, teachers implement adaptive strategies through personal approaches and individual dialogue. The main conclusion confirms that the synergy between pedagogical competence, emotional maturity, and supportive leadership support is a determining factor in educational quality. Humanistic teacher professionalism has been proven to create a conducive learning ecosystem and serve as a primary foundation for character formation and student academic success amidst various resource limitations in a comprehensive, equitable, and sustainable manner. ABSTRAK Tantangan pendidikan abad ke-21 menuntut penguatan profesionalisme guru yang melampaui aspek akademik, terutama di sekolah dengan keterbatasan sarana seperti SMA Negeri 1 Waigete. Penelitian ini bertujuan menganalisis implementasi profesionalisme guru dalam meningkatkan kualitas pembelajaran melalui kompetensi, keteladanan, dan kepemimpinan humanis. Menggunakan pendekatan kualitatif deskriptif, tahapan penelitian yang dilaksanakan pada Januari 2026 ini meliputi wawancara mendalam, observasi, dan dokumentasi terhadap kepala sekolah serta guru yang dipilih melalui purposive sampling. Temuan penelitian menunjukkan bahwa profesionalisme tercermin dari keterlibatan guru dalam pengembangan sekolah serta pengelolaan kecerdasan emosional dan sosial. Penggunaan metode ceramah, diskusi kelompok kecil, serta praktikum terbukti meningkatkan partisipasi aktif dan disiplin siswa. Meskipun menghadapi kendala berupa rendahnya motivasi belajar dan keberagaman karakter peserta didik, guru menerapkan strategi adaptif melalui pendekatan personal dan dialog individual. Simpulan utama menegaskan bahwa sinergi antara kompetensi pedagogik, kematangan emosi, dan dukungan kepemimpinan suportif merupakan faktor penentu mutu pendidikan. Profesionalisme guru yang humanis terbukti mampu menciptakan ekosistem belajar kondusif sekaligus menjadi fondasi utama dalam pembentukan karakter serta kesuksesan akademik siswa di tengah berbagai keterbatasan sumber daya secara komprehensif, merata dan juga berkelanjutan.